A Theoretical & Practical Project-Based Questionnaire for the Mining Industry Risks - Mostafavi, Mostafa; Haji, Alireza; Fallahifard, Ali (Annals of Process Engineering and Management, 2026)
As mining industry is one of the deadliest industries in the world there are many risks in different types (categories), which they are involved in it. Here we have dedicated all efforts in order to develop a questionnaire in a way that: 1) it encompasses all the risks in order (phase by phase), and 2) the risks are addressed according to Project Management Body of Knowledge (PMBOK) approach. Ultimately the risks are prioritized using a novel fuzzy score-based theoretical method and addressed to minimize the casualties. As proof of concept, a case study was conducted in the mining industry upon the questionnaire.